2015
DOI: 10.1177/0735633115588774
|View full text |Cite
|
Sign up to set email alerts
|

Affect in Embodied Pedagogical Agents

Abstract: Over the past decade, computer games and other interactive technologies have shown great potential when used in innovative ways to enhance learning. It is now known that learning is associated not only with cognitive ability but also with affect. The incorporation of affective embodied pedagogical agents (EPAs) in computer programs for learning can significantly influence learner beliefs and efficacy. However, there have been a number of criticisms and contradictory empirical findings calling into question ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(24 citation statements)
references
References 57 publications
(59 reference statements)
2
21
0
1
Order By: Relevance
“…Derived as an extension of intelligent tutoring systems [1,2], they are seen as potential tools to create a social presence that primes learners to deeply process the learning material (social agency theory, [1,2]). The social agency theory is supported by findings of a recent meta-analysis; it was revealed that learners achieved more from multimedia learning system with a pedagogical agent than a system without an agent (see for a review [3]).…”
Section: Introductionmentioning
confidence: 99%
“…Derived as an extension of intelligent tutoring systems [1,2], they are seen as potential tools to create a social presence that primes learners to deeply process the learning material (social agency theory, [1,2]). The social agency theory is supported by findings of a recent meta-analysis; it was revealed that learners achieved more from multimedia learning system with a pedagogical agent than a system without an agent (see for a review [3]).…”
Section: Introductionmentioning
confidence: 99%
“…Pedagogical agents are visual characters that reside within the digital space of virtual learning systems. They are viewed as intrinsically social interfaces, which allows for the inclusion of socio-emotive values in the learning process (Guo & Goh, 2015;Kim & Baylor, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Analyzing user needs [21] [22] MRT1: SPAM should first start with analyzing the user in detail Error handling [23] [24] MRT2: SPAM should provide the developer guidance on how to include error handling menchanisms into the SPA so that the user will not get frustrated and can continue the interaction. Modeling interaction process [25] [26] MRT3: SPAM should guide the developer to model the interaction process that users should run through before technically implementing the SPA.…”
Section: Meta-requirements From Theorymentioning
confidence: 99%